Analisis Tingkat Risiko Bahaya pada Proses Pengiriman Bahan Bakar Minyak (BBM) MenggunakanMetode Hazard Identification Risk Assessment (HIRA) - Sindy Anggraeni; Agustian Suseno (LPPM Akademi Minyak dan Gas Balongan Indramayu, 2022)
In preventing work accidents in every work activity, it is necessary to look at the causes of hazards and risks that may be caused by the work. In this research, the hazard operability study method is applied to assist in finding the cause and determining the adverse consequences and actions that can be taken to reduce the impacts and risks that have been identified in the process of delivering fuel oil at PT. XYZ. There are two variables studied, namely likelihood and severity. Data collection techniques using observation and interviews. Observational data collection method is done by direct observation to the work area to get the actual data needed in this research. Interviews were conducted directly with safety officers at the company. After identification, there are 24 potential hazards that can cause work accidents. The highest risk level is 46% in the high risk category and the extreme risk level is in the fuel delivery process with the hazard source being road conditions. Improvement refers to the hierarchy of hazard control namely elimination, administrative controls and personal protective equipment.